Economic Perspective of Trends and Determinants of Paddy Stubble Burning in North Western India - Jambagi, Ragini; Dharam Raj Singh,; Alka Singh,; Vinay Kumar Sehgal,; Giridhar, BJ (Indian Journal of Extension Education, 2025)
During the paddy harvesting season in North-Western India, a significant smog problem occurs due to the unhealthy practice of stubble burning, which also reduces soil fertility. The government has implemented various efforts to lessen its severity. By using tabular analysis of burning events, this study found that the number of such events decreased from 2016 to 2021 in North-Western India. The Mann-Kendall test indicated a negative trend in burning events for the three states of Punjab, Haryana, and WUP. In Punjab, about 49% of the paddy area is burned, with the growth rates of the burnt area and paddy area being nearly equal. Conversely, in Haryana, only 17% of the paddy area is burned, but its burnt area is growing at a faster rate than the paddy area itself. Districts like Firozepur, Faridkot, Patiala, and Sangrur in Punjab, along with Fatehabad, Kurukshetra, and Karnal in Haryana, require special attention due to their relatively high percentage of paddy area subjected to burning. Panel regression analysis suggests that cultivating potato and basmati rice can reduce the paddy area affected by burning.